A garantia do direito à saúde ao paciente fora de domicílio: uma proposta de efetivação do direito à saúde a partir da análise dos processos do estado do Tocantins em 2018 e 2019 - Kühn, Vânia Márcia Rocha Pinheiro Lima (Universidade Federal do Tocantins, 2024)
The objective of this dissertation is to analyze the effectiveness of the judicial decisions handed down in the State of Tocantins, which seek to guarantee access to out-of-home treatment. The quanti-qualitative method proved to be the most appropriate for the proposed objectives, and data collection was performed by analyzing the judicial proceedings underway in the State of Tocantins, whose decisions have been granted in advance or with in-depth examination, as well as have occurred between January 1, 2018 to December 20, 2019, always through the database of the State Justice of Tocantins (E-proc). In addition to the results obtained with the application of the data collection instrument, a varied bibliographic material was used through consultations to books, scientific articles, legislation, judgments of Superior Courts and websites.